Study On The Perceived Effectiveness Of The Malaysian Armed Forces K-Force Programme - Palanisamy, Rathika (2009)
This paper investigates the three elements that determine the perceived effectiveness of the programme which is the access to the e-learning modules, design of the e-learning modules and their satisfaction level with the programme.